Structural and mechanical properties of cardiolipin lipid bilayers determined using neutron spin echo, small angle neutron and X-ray scattering, and molecular dynamics simulations. Issue 1 (5th November 2014) - Pan, Jianjun; Cheng, Xiaolin; Sharp, Melissa; Ho, Chian-Sing; Khadka, Nawal; Katsaras, John
Abstract : Determining structural and mechanical properties of cardiolipin lipid bilayers using a multitude of experimental and computational approaches. Abstract : The detailed structural and mechanical properties of a tetraoleoyl cardiolipin (TOCL) bilayer were determined using neutron spin echo (NSE) spectroscopy, small angle neutron and X-ray scattering (SANS and SAXS, respectively), and molecular dynamics (MD) simulations. We used MD simulations to develop a scattering density profile (SDP) model, which was then utilized to jointly refine SANS and SAXS data. In addition to commonly reported lipid bilayer structural parameters, component distributions were obtained, including the volume probability, electron density and neutron scattering length density. Of note, the distance between electron density maxima D HH (39.4 Å) and the hydrocarbon chain thickness 2 D C (29.1 Å) of TOCL bilayers were both found to be larger than the corresponding values for dioleoyl phosphatidylcholine (DOPC) bilayers. Conversely, TOCL bilayers have a smaller overall bilayer thickness D B (36.7 Å), primarily due to their smaller headgroup volume per phosphate. SDP analysis yielded a lipid area of 129.8 Å 2, indicating that the cross-sectional area per oleoyl chain in TOCL bilayers ( i.e., 32.5 Å 2 ) is smaller than that for DOPC bilayers. Multiple sets of MD simulations were performed with the lipid area constrained at different values. The calculated surface tension versus lipid area resulted in a lateral area compressibility modulus K A of 342 mN m −1, which is slightly larger compared to DOPC bilayers. Model free comparison to experimental scattering data revealed the best simulated TOCL bilayer from which detailed molecular interactions were determined. Specifically, Na + cations were found to interact most strongly with the glycerol hydroxyl linkage, followed by the phosphate and backbone carbonyl oxygens. Inter- and intra-lipid interactions were facilitated by hydrogen bonding between the glycerol hydroxyl and phosphate oxygen, but not with the backbone carbonyl. Finally, analysis of the intermediate scattering functions from NSE spectroscopy measurements of TOCL bilayers yielded a bending modulus K C of 1.06 × 10 −19 J, which was larger than that observed in DOPC bilayers. Our results show the physicochemical properties of cardiolin bilayers that may be important in explaining their functionality in the inner mitochondrial membrane.